http://isrctn.com/ 2014
DOI: 10.1186/isrctn13188513
|View full text |Cite
|
Sign up to set email alerts
|

Twenty weeks of home-based interactive training of children with cerebral palsy improves functional abilities

Abstract: Background: Home-based training is becoming ever more important with increasing demands on the public health systems. We investigated whether individualized and supervised interactive home-based training delivered through the internet improves functional abilities in children with cerebral palsy (CP). Methods: Thirty four children with CP (aged 9-16; mean age 10.9 ± 2.4 years) (GMFCS I-II; MACS I-II) were included in this non-randomized controlled clinical training study. 12 children (aged 7-16; mean age: 11.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Move it to improve it (Mitii; Mitii Development A/S, Copenhagen, Denmark) is a web‐based therapy program that combines upper‐limb, visual–perceptual, and lower‐limb strength training using a game‐like design delivered in the client's home. The feasibility of the program has been confirmed in a non‐randomized study ( n =34), with participants demonstrating significant gains in functional strength …”
mentioning
confidence: 88%
“…Move it to improve it (Mitii; Mitii Development A/S, Copenhagen, Denmark) is a web‐based therapy program that combines upper‐limb, visual–perceptual, and lower‐limb strength training using a game‐like design delivered in the client's home. The feasibility of the program has been confirmed in a non‐randomized study ( n =34), with participants demonstrating significant gains in functional strength …”
mentioning
confidence: 88%
“…It remains unclear whether children with traumatic brain injury, non-traumatic brain injury or stroke respond differently to Mitii TM and how this compares to similar studies investigating the effectiveness of Mitii TM in children with unilateral cerebral palsy. 10,11…”
Section: Discussionmentioning
confidence: 99%
“…10 A smaller non-randomized study of children aged 9 to 16 years ( n = 34) with cerebral palsy demonstrated that Mitii TM improved in functional strength tests for the lower limb ( p < 0.05) compared with an age-matched control group ( n = 12). 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of the program has been demonstrated in a small non-randomised pilot study of children aged 9-13 years with Unilateral Cerebral Palsy. 13 It has not been evaluated in the paediatric acquired brain injury population. There is potential value of implementing this rehabilitation intervention in children and adolescents with an acquired brain injury who also experience cognitive, perceptual, and motor difficulties.…”
Section: Introductionmentioning
confidence: 99%